THE INFLUENCE OF WORK ENVIRONMENT, WORK MOTIVATION, AND COMPENSATION ON EMPLOYEE PERFORMANCE AT WAROENG SPECIAL SAMBAL - Lusiana Rahayu; Didik Subiyanto; Ignatius Soni Kurniawan (IAIN Surakarta, 2021)
The basic problem in a business company is how to spur employee performance to always improve. This problem is also experienced by companies with types of food stalls, namely Waroeng Special Sambal (SS). Strong suspicions, lack of attention to aspects of work comfort, work encouragement, and material feedback are crucial factors for the stagnant performance of employees in the company. This study was conducted to measure the level of influence of the work environment, work motivation, and compensation on the employee’s performance of Waroeng SS. This study was an ex-post facto study using quantitative approach. A total of 80 special chili employees in the province of Yogyakarta were involved as research samples. Data collection was carried out by using a questionnaire with a 4 Likert scale questionnaire instrument. The collected data were analyzed by using multiple linear regression analysis. The results of the analysis of research data indicate that the work environment, work motivation, and compensation have a significant influence on employee performance. It is very important for Waroeng Special Sambal to pay attention to improving aspects of the quality of the work environment, strengthening work motivation, and providing competence to employees. Thus, if these three aspects are met, employee performance can also increase.